ANTIBACTERIAL, ANTIOXIDANT, AND PHYTOCHEMICAL PROPERTIES OF BRYOPHYLLUM PINNATUM (LAM.) LEAF EXTRACTS AGAINST PATHOGENIC BACTERIA - Elizabeth Tomilayo Akinterinwa; Babayemi Olawale Oladejo; Muftau Kolawole Oladunmoye (Faculty of Vocational Studies, Universitas Airlangga, 2025)
Background: Bryophyllum pinnatum (Lam.) (Family: Crassulaceae), also known as Kalanchoe pinnatum, is a perennial herb, 3 to 5 meters tall, with opposed glabrous leaves. It is used to treat various illnesses due to its many health benefits. Purpose: This study aims to investigate the biological importance of B. pinnatum leaf extracts against some pathogenic bacteria. Method: Freshly harvested leaves of B. pinnatum were collected, air-dried, pulverized to powder and stored in air-tight containers using standard methods. Extracts were obtained from the powder using ethanol, ethyl acetate and distilled water. Pathogenic bacterial isolates were collected and their identity were confirmed using colonial and biochemical tests. The extracts were screened for antibacterial, antioxidant and phytochemical potentials using standard methods. Result: The highest percentage yield was obtained with the ethanol extract (12.2%) of B. pinnatum and the lowest yield (5.3 %) was obtained with the ethyl acetate extract. The ethanol extract was effective against eight (8) out of the thirteen test isolates, while the aqueous extract had the lowest activity and was effective against only two bacteria (Pseudomonas aeruginosa and Haemophillus influenzae). The lowest MIC observed with the three extracts is 25 mg/ml. B. pinnatum leaf extracts possess high antioxidant properties that are concentration dependent. The phytochemical constituents that were recorded in this study include saponins, terpenoids, steroids, tannins and glycosides. Steroid was present in only the ethanol extract but absent in the other two. Conclusion: B. pinnatum leaves have antibacterial, antioxidant and phytochemical properties and could be further utilized to manage bacterial infections.